Assessment of the way the type of moral climate of public administration institutions is dependent on the development of moral reasoning of the decision makers in terms of social expectations - Mroziewski, Marian (Journal of Public Governance, 2014)
The paper presents an analysis of the postulated and identified moral attitudes of decision makers from national state administration and local government institutions and the impact of these attitudes on the development of the moral climate in the public institutions surveyed. The strength and direction of the impact of moral attitudes of these managers on moral climate was described using Spearman’s statistics. The present study also shows the attitudes of officials in the performance of their social mission related to public administration, where a certain level of moral competence of decision makers is expected, and moral climate is supposed to develop.